P626 Anti-TNF monotherapy is associated with an adverse clinical outcome in female Inflammatory Bowel Disease patients who stop Anti-TNF treatment during the third trimester of pregnancy. (21st January 2022) - Lastiri, E; Herrera-De Guise, C; Casellas, F; Mayorga, L; Robles, V; Cespedes, E; Perez, Z; Oller, E; Borruel-Sainz, N
Abstract: Background: Anti-TNF drugs are safe during pregnancy in inflammatory bowel disease (IBD), but they cross the placenta most actively in the third trimester, and some guidelines still recommend stopping them during this period. There few data that examines the impact of anti-TNF discontinuation on the clinical course of IBD, so we aimed to explore the clinical outcomes of IBD pregnant patients who stopped anti-TNF at the third trimester. Methods: We performed a retrospective, longitudinal study on female IBD patients receiving anti-TNF agents at our IBD clinic. We included IBD pregnant patients who discontinued the anti-TNF in the third trimester of pregnancy, and we matched these cases in a 1:1 ratio with non-pregnant female IBD patients by age, type of IBD, type of anti-TNF, duration of treatment, location, and behavior of IBD. Demographic and clinical variables were collected from 18 months before anti-TNF discontinuation and 12 months after discontinuation, and when available endoscopic indices (SES CD and UC). We determined whether subjects presented any adverse clinical outcome during the follow-up defined as development of disease flare, corticosteroid use, hospital admission, need for surgery, biologic dose escalation, or switch. Results: We included 34 pregnant patients and 34 controls. Patients who stopped anti-TNF more frequently presented an adverse clinical outcome during the follow-up year when compared to the control group (47.1% vs. 23.5% p = 0.04) and flare activity (35, 3 vs. 11.8%, p = 0.02). We found no differences in escalation or biologic switch, hospital admission, or surgery between the subjects. We also found an association between the development of an adverse clinical outcome and anti-TNF monotherapy (p=0.009) and a higher SESCD in the previous year (p=0.017). In the multivariate analysis, anti-TNF monotherapy was the only independent factor for developing an adverse clinical outcome up to 1 year after anti-TNF discontinuation (OR: 3.47, CI 95%: 1.16–10.4, p=0.026). Conclusion: In our cohort of female IBD patients on anti-TNF, monotherapy was independently associated with an adverse clinical outcome in the following year after anti-TNF discontinuation.